Natural radioactivity in building materials in the European Union: a database and an estimate of radiological significance - Trevisi, R.; Risica, S.; D’Alessandro, M.; Paradiso, D.; Nuccetelli, C. (Journal of environmental radioactivity, 2012)
The authors set up a database of activity concentration measurements of natural radionuclides ( 226Ra, 232Th and 40K) in building material. It contains about 10,000 samples of both bulk material (bricks, concrete, cement, natural- and phosphogypsum, sedimentary and igneous bulk stones) and superficial material (igneous and metamorphic stones) used in the construction industry in most European Union Member States. The database allowed the authors to calculate the activity concentration index I – suggested by a European technical guidance document and recently used as a basis for elaborating the draft Euratom Basic Safety Standards Directive – for bricks, concrete and phosphogypsum used in the European Union. Moreover, the percentage could be assessed of materials possibly subject to restrictions, if either of the two dose criteria proposed by the technical guidance were to be adopted. ► A database of natural radioactivity in building material was set up. ► It contains data related to 10,000 samples of both products and materials in EU. ► The activity concentration index I, suggested by the EU RP112 was computed. ► The adoption of the dose criterion of 0.3 mSv y −1 of the EU RP112 is too ambitious. ► A health goal of 1 mSv y −1 appears more realistic.